Performance of the Visual Analogue Scale of Happiness and of the Cornell Scale for Depression in Dementia in the Tremembé Epidemiological Study, Brazil - Karolina G. César; Sonia M.D. Brucki; Leonel T. Takada; Luiz Fernando C. Nascimento; Camila M.S. Gomes; Milena C.S. Almeida; Maira O. Oliveira; Fábio H.G. Porto; Mirna L.H. Senaha; Valéria S. Bahia; Thaís Bento L. Silva; Jéssica N. Ianof; et al. (Dementia & Neuropsychologia)
Depression is a major growing public health problem. Many population studies have found a significant relationship between depression and the presence of cognitive disorders. OBJECTIVE: To establish the correlation between the Visual Analogue Scale of Happiness and the Cornell Scale for Depression in Dementia in the population aged 60 years or over in the city of Tremembé, state of São Paulo, Brazil. METHODS: An epidemiological survey involving home visits was carried out in the city of Tremembé. The sample was randomly selected by drawing 20% of the population aged 60 years or older from each of the city's census sectors. In this single-phase study, the assessment included clinical history, physical and neurological examination, cognitive evaluation, and application of both the Cornell Scale and the Analogue Scale of Happiness for psychiatric symptoms. The presence of depressive symptoms was defined as scores greater than or equal to 8 points on the Cornell Scale. RESULTS: A total of 623 subjects were evaluated and of these 251 (40.3%) had clinically significant depressive symptoms on the Cornell Scale, with a significant association with female gender (p<0.001) and with lower education (p=0.012). One hundred and thirty-six participants (21.8%) chose the unhappiness faces, with a significant association with age (p<0.001), female gender (p=0.020) and low socioeconomic status (p=0.012). Although there was a statistically significant association on the correlation test, the correlation was not high (rho=0.47). CONCLUSION: The prevalence of depressive symptoms was high in this sample and the Visual Analogue Scale of Happiness and Cornell Scale for Depression in Dementia should not be used as similar alternatives for evaluating the presence of depressive symptoms, at least in populations with low educational level.